2008
DOI: 10.1002/elps.200800422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic diversity within Cryptosporidium hominis and Cryptosporidium parvum from imported and autochtonous cases of human cryptosporidiosis by mutation scanning

Abstract: The present study investigated sequence variation in part of the 60 kilodalton glycoprotein (pgp60) gene among Cryptosporidium hominis and Cryptosporidium parvum isolates (n=115) from citizens of the UK inferred to have been infected whilst travelling abroad (to 25 countries) or in the UK. The genomic DNA samples from these isolates were subjected to PCR-coupled single-strand conformation polymorphism analysis, followed by targeted sequencing of pgp60. Individual samples were classified to the genotypic and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 83 publications
2
18
0
1
Order By: Relevance
“…Recent studies have demonstrated the utility of SSCP for the rapid and cost effective analysis of nucleotide variation in pgp60 ($350-450 bp) [18][19][20][21] and other loci [5]. These investigations have shown consistent differentiation among subgenotypes differing by as little as a single-nucleotide substitution in the TCA microsatellite region, reinforcing the high-mutation detection capacity of this analytical approach for amplicons in this size range [5,[18][19][20][21]. However, the mutation detection capacity of SSCP can decrease substantially for larger amplicons [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated the utility of SSCP for the rapid and cost effective analysis of nucleotide variation in pgp60 ($350-450 bp) [18][19][20][21] and other loci [5]. These investigations have shown consistent differentiation among subgenotypes differing by as little as a single-nucleotide substitution in the TCA microsatellite region, reinforcing the high-mutation detection capacity of this analytical approach for amplicons in this size range [5,[18][19][20][21]. However, the mutation detection capacity of SSCP can decrease substantially for larger amplicons [6].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from ruminant faecal samples was isolated using the PowerSoil kit (MoBio), according to manufacturer's instructions. The genomic DNA samples had been classified to species based on PCR-based SSCP and/or sequencing of loci in the small subunit (SSU) and second internal transcribed spacer (ITS-2) of nuclear ribosomal DNA and/or gp60 [18][19][20]24].…”
Section: Parasites and Isolation Of Genomic Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…Differentiating Cryptosporidium species and diagnosing C. parvum genotypes is impossible using microscopy due to the morphological similarities between the oocysts of the various species and their subtypes (Jex and Gasser 2008;Fayer 2010;Das et al 2011). Therefore, molecular tools are being increasingly used to detect and differentiate between Cryptosporidium species and subtypes (Xiao 2010).…”
mentioning
confidence: 99%